10q23.31 microduplication encompassing PTEN decreases mTOR signalling activity and is associated with autosomal dominant primary microcephaly. Issue 8 (9th October 2018) - Oliveira, Danyllo; Leal, Gabriela Ferraz; Sertié, Andréa L; Caires Jr, Luiz Carlos; Goulart, Ernesto; Musso, Camila Manso; Oliveira, João Ricardo Mendes de; Krepischi, Ana Cristina Victorino; Vianna-Morgante, Angela Maria; Zatz, Mayana
Abstract : Background: Hereditary primary microcephaly (MCPH) is mainly characterised by decreased occipitofrontal circumference and variable degree of intellectual disability. MCPH with a dominant pattern of inheritance is a rare condition, so far causally linked to pathogenic variants in the ALFY, DPP6, KIF11 and DYRK1A genes. Objective: This study aimed at identifying the causative variant of the autosomal dominant form of MCPH in a Brazilian family with three affected members. Methods: Following clinical evaluation of two sibs and their mother presenting with autosomal dominant MCPH, array comparative genome hybridisation was performed using genomic DNA from peripheral blood of the family members. Gene and protein expression studies were carried out in cultured skin fibroblasts. Results: A 382 kb microduplication at 10q23.31 was detected, encompassing the entire PTEN, KLLN and ATAD1 genes. PTEN haploinsufficiency has been causally associated with macrocephaly and autism spectrum disorder and, therefore, was considered the most likely candidate gene to be involved in this autosomal dominant form of MCPH. In the patients' fibroblasts, PTEN mRNA and protein were found to be overexpressed, and the phosphorylation patterns of upstream and downstream components of the mammalian target of rapamycin (mTOR) signalling pathway were dysregulated. Conclusions: Taken together, our results demonstrate that the identified submicroscopic 10q23.31 duplication in a family with MCPH leads to markedly increased expression of PTEN and reduced activity of the mTOR signalling pathway. These results suggest that the most probable pathomechanism underlying the microcephaly phenotype in this family involves downregulation of the mTOR pathway through overexpression of PTEN .